Effect of Psychoeducational on Athletic Identity among Adolescent Taekwondo Athletes - Shavilla Adera Nazza Anjani; Mulyana; Ivan Rivan Firdaus (Universitas Negeri Semarang, 2025)
Most athletes begin their professional careers at a young age facing complex academic, social, and athletic demands, particulary during adolescence. These conditions make the formation of athletic identity a dynamic to process that is prone to athletic identity crises, especially among taekwondo athletes. This study aims to examine effect of psychoeducational on athletic identity among adolescent taekwondo athletes. The research method used was an experiment with a pretes-postest control group design. The research subject were 20 taekwondo athletes aged 18-21 years, divided into a experimental group and a control group. The experimental group was given psychoeducational intervention, which include psychological education, stress management, motivation enhancement, and coping techniques for four weeks, while tnhe control group was not given any treatment. Athletic identity was measured using the Athletic Identity Measurement Scale (AIMS). Data were analyzed using SPSS version 26. The result of the Independent samples T-Test showed a significant difference between the experimental and the control groups, with a p – value of 0.003 (p < 0.05). The results of this study indicate a significant effect. These findings indicate that psychoeducational significantly athletic identity of adolescent taekwondo athletes.